Współczesne ukraińskojęzyczne teksty internetowe jako generator innowacji przysłowiowych (aspekt tekstologiczno-pragmatyczny) - Szutkowski, Tomasz (Przegląd Wschodnioeuropejski, 2024)
In the article the Author analyses modern proverb modifications in the context of the assumptions of contextual studies within paremiology. Research material was excerpted from internet sources in the Ukrainian language that feature an especially dynamic process of creation of innovations based on canonical proverbs functioning in Ukrainian. This research is a continuation of analyses of modern tendencies in the European paremiology. Textological- -pragmatical approach treats proverbs as situational macrosigns that have a wide range of usage in texts. Proverb modifications indicate that paremiology is still an active pragmatic form of verbalisation of varied messages that is effectively used by speakers in numerous texts and contexts.